PELATIHAN PENINGKATAN KEMAMPUAN GURU DALAM PEMBELAJARAN MATEMATIKA DI MADRASAH IBTIDAIYAH SE-KECAMATAN TAMBANG KABUPATEN KAMPAR - Aryani, Fitri; Marzuki, Corry Corazon; Suryani, Irma (JRCE (Journal of Research on Community Engagement), 2019)
This paper contains the results of community service conducted by the implementation team of Madrasah Ibtidaiyah teachers in Tambang District, Kampar Regency. Here the community service team wants to improve the ability of teachers to provide teaching and understanding of mathematics to students later by using the GASING Method. The results obtained that there was an increase in the teachers present as participants by looking at the results of the pre-test and post-test that have been done. This result can be seen that starting with H0, that is, significant pre-test scores are smaller than post-test scores. That is, the teachers who attended were faster and more precise in answering the questions given than before they knew GASING.